2019
DOI: 10.1186/s13046-019-1326-5
|View full text |Cite
|
Sign up to set email alerts
|

Soluble fibrinogen-like protein 2 promotes the growth of hepatocellular carcinoma via attenuating dendritic cell-mediated cytotoxic T cell activity

Abstract: Background Soluble fibrinogen-like protein 2 (sFGL2), a secretory protein expressed by regulatory T cells (Tregs) with immunosuppressive activity, is highly expressed in both the peripheral blood and tumor tissue of patients with hepatocellular carcinoma (HCC); however, sFGL2 function in HCC remains largely unknown. Here, we elucidated the potential role of sFGL2 in HCC progression. Methods T cells, dendritic cells (DCs), and related cytokines in the tumor microenvironm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…It is unknown whether frequent FGL2 expression in GIST hinders the clinical efficiency of checkpoint inhibitors. FGL2 mediates a wide variety of immunological effects and sFGL2 is immunosuppressive, and could, therefore, promote cancer growth 9,22 . In this study, FGL2 expression was associated with low numbers of tumour‐infiltrating CD3+, CD8+, CD20+ and Foxp3+ lymphocytes, which is in agreement with the immunosuppressive role of sFGL2 9 .…”
Section: Discussionsupporting
confidence: 84%
“…It is unknown whether frequent FGL2 expression in GIST hinders the clinical efficiency of checkpoint inhibitors. FGL2 mediates a wide variety of immunological effects and sFGL2 is immunosuppressive, and could, therefore, promote cancer growth 9,22 . In this study, FGL2 expression was associated with low numbers of tumour‐infiltrating CD3+, CD8+, CD20+ and Foxp3+ lymphocytes, which is in agreement with the immunosuppressive role of sFGL2 9 .…”
Section: Discussionsupporting
confidence: 84%
“…FGL2, also known as FGL2 prothrombinase, is a member of the fibrinogen-related protein superfamily [ 40 ]. FGL2 was reported to be not only significantly increased in hepatitis [ 41 , 42 ] and nonalcoholic fatty liver [ 43 ] but also highly expressed in liver cancer [ 44 , 45 ]. The results of Liu indicated that knocking out FGL2 expression can significantly inhibit the growth of liver implant tumors and slow down the progression of liver cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…sFGL2 inhibited macrophages by binding to FcγRIIB receptor to block the release of monocyte chemoattractant protein-1 (MCP-1), and by suppressing the activation of c-Jun N-terminal kinase 53 . sFGL2 can restrain the expression of MHCII, CD40, CD80, CD86, and CD83 in bone marrow derived mesenchymal stem cells in vitro by inhibiting the phosphorylation of Akt, NFκB, cAMP response element binding protein (CREB), and p38 in DC, and can decrease the cytotoxicity in HCC tissues and reinforce the burden of tumor 54 . sFGL2 levels were detected for the first time in the Egyptian HCV-infected and HCC patients, which provided a potential immune target for the treatment of HCV and HCC in the future ( Figure 2 ) 55 .…”
Section: Structure and Functionmentioning
confidence: 99%